1999
DOI: 10.1074/jbc.274.50.35734
|View full text |Cite
|
Sign up to set email alerts
|

How an Inhibitor of the HIV-I Protease Modulates Proteasome Activity

Abstract: The human immunodeficiency virus, type I protease inhibitor Ritonavir has been used successfully in AIDS therapy for 4 years. Clinical observations suggested that Ritonavir may exert a direct effect on the immune system unrelated to inhibition of the human immunodeficiency virus, type I protease. In fact, Ritonavir inhibited the major histocompatibility complex class I restricted presentation of several viral antigens at therapeutically relevant concentrations (5 M). In search of a molecular target we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 35 publications
4
105
0
1
Order By: Relevance
“…This immunomodulatory effect was neither due to the inhibition of viral replication nor to a direct effect on CTL activation, but was attributed to a reduction in the presentation of immunodominant LCMV epitopes. Interestingly, Ritonavir was found to inhibit the chymotrypsin-like activity of the 20S proteasome in vitro, while the trypsin-like activity was enhanced (41,42). We reasoned that the modulation of proteasome activity would account for the in vivo reduction of Ag presentation, but we could not exclude that this effect was, at least in part, due to the inhibition of other proteases in APC.…”
Section: Discussionmentioning
confidence: 94%
“…This immunomodulatory effect was neither due to the inhibition of viral replication nor to a direct effect on CTL activation, but was attributed to a reduction in the presentation of immunodominant LCMV epitopes. Interestingly, Ritonavir was found to inhibit the chymotrypsin-like activity of the 20S proteasome in vitro, while the trypsin-like activity was enhanced (41,42). We reasoned that the modulation of proteasome activity would account for the in vivo reduction of Ag presentation, but we could not exclude that this effect was, at least in part, due to the inhibition of other proteases in APC.…”
Section: Discussionmentioning
confidence: 94%
“…This investigation was warranted, particularly because Liu et al (10) had reported an association of FAT10 with MAD2, which is a protein involved in mitotic arrest. We stained nuclei of viable TB1N cells with propidium iodide 1 or 2 days after FAT10 induction, and the DNA content was assessed by flow cytometry as described previously (18). In this analysis, no change in the distribution of DNA content in TB1N cells could be observed when cells grown in the absence or presence of tet were compared (data not shown).…”
Section: Fat10 Induction Does Not Affect Cell Surface Expression Of Mmentioning
confidence: 98%
“…For cell cycle analysis, nuclei were prepared from TB1N cells 0, 24, and 48 h after the induction of FAT10 expression, and nuclei were stained with propidium iodide exactly as described previously (18). Fluorescence of cells or nuclei was analyzed using a FACScan flow cytometer and LYSIS II software (Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%
“…Proteasome inhibition has been shown for atazanavir, indinavir, lopinavir, nelfinavir, ritonavir, and saquinavir, although the potency of this inhibitory effect seemed variable between these drugs (Schmidtke et al. 1999; Pajonk et al. 2002; Piccinini et al.…”
Section: Introductionmentioning
confidence: 99%